Strengthening the Philippine rice seed system - Sombilla, Mercedita A.; Quilloy, Karen (International Food Policy Research Institute, 2014)
This brief aims to identify the factors contributing to low certified seed use by evaluating the evolution of rice seed varieties, analyzing the trends in seed adoption, and describing the Philippine seed system and its regulatory structure. It concludes with a summary of these issues leading to key recommendations to improve and strengthen the rice seed industry.